Foreign Direct Investment in a Developing Economy : The Malaysian Perspective - Devan, Iyavoo (2000)
The objective of the study is to investigate and analyze the trend pattern, determinants and impact of FDI in Malaysia vis-a-vis in ASEAN settings over the period of 1985 to 1999. The theoretical underpinning of the FDI role in Malaysia is explored as background of the study. The empirical study was carried out by linear regression model (OLR) and tested with ANOVA method. Our results show an increasing trend of public and private investment in the country over the years. However, the growth of private investment in the flow of FDI has out paced the rise inpublic investment, 1992 onwards. The macroeconomic variables such as GDP, GNI, employment and exports are found to be positively influenced by the growth of FDI in Malaysia. FDI is an engine of growth for the Malaysian economy. For sustained flow of FDI, we suggest the policy-makers should maintain price stability and macroeconomic balance with effective policy measures combined with good governance and accelarating growth rate of the economy.